Constraint Therapy with and Without Virtual Reality for Children with Unilateral Cerebral Palsy: A Randomized Trial - Heather Roberts; Nancy J. Clegg; Wayni Wang; Sydney Chapa; Briana Arellano; Madison Trahan; Fabiola Reyes; Mauricio R. Delgado; Sue Ram; Angela Shierk (Children)
Background/Objectives: Cerebral palsy (CP) is the most common childhood motor disorder, with unilateral cerebral palsy (UCP) presenting with asymmetrical motor function that can cause decreased upper limb function. Constraint-Induced Movement Therapy (CIMT) is an evidence-based intervention that addresses upper limb functional limitations, but further study on combining interventions with CIMT is warranted. Combining CIMT with virtual reality (VR) is hypothesized to enhance engagement and therapeutic outcomes. This study compared the effectiveness of CIMT alone versus CIMT combined with VR (CIMT + VR) in improving upper limb function and occupational performance in children with UCP. Methods: A blinded, randomized, controlled trial included children aged 5–13 years with Manual Ability Classification System (MACS) levels I–III. The participants were randomized into CIMT or CIMT + VR groups and completed a standardized 10-day camp protocol (60 h). Pre-intervention and post-intervention assessments included the Assisting Hand Assessment (AHA) and the Canadian Occupational Performance Measure (COPM). Secondary measures included acceptability ratings of VR devices and fidelity. Results: Thirty-two participants, with a mean age of 9 years and 3 months (3 years 1 month), MACS I = 4, II = 20, and III = 8, completed this study. CIMT and CIMT + VR led to significant improvements in upper limb function, with no statistically significant differences between the groups in bilateral hand use and occupational performance. Conclusions: These findings reinforce the efficacy of CIMT while highlighting the potential of VR to enhance engagement when the child prefers to interact with the technology, underscoring the importance of individualized approaches that consider a child’s preferences and responsiveness to different intervention modalities.